Selling English: advertising as a phonopragmatic medium for teaching intonation use - Demina, Malvina A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Advertising is among the most dynamic engines of language innovation, a “living” laboratory of catch-phrases and slang that give insight into modern social attitudes and developments. This study argues that advertising is an underappreciated resource for effective teaching of suprasegmental characteristics. It aims to embrace advertising, a central component of the media and cultural landscape, as the basis for a phonopragmatic tool that expands students' understanding of the persuasive power of pitch variability. The linguistical part of the study combines auditory and acoustic types of complex phonetic analysis of 30 advertisement videos. The results testify to the strategic use of intonational and prosodic means in advertising discourse that reflect differing approaches to audiences. Variations in pitch help convey explicit messages directed at rational thinking, or foster more intimate conversational approaches aiming to influence the emotional dimension. The findings of the linguistic analysis contribute to the scientific description of advertising discourse as a multimodal category and assist in the teaching of intonation in more appealing forms to the students who may be inhibited by interference from their native language (L1). Acquiring prosodic strategies of a second language (L2) through the familiar medium of advertising may represent an additional incentive for teachers and learners, as part of communicative phonetics that emphasizes the pragmatic impact of various intonation combinations in coherent discourse. This approach diversifies traditional phonetic drills of separate pitch patterns and reinforces the focus on students’ L2 comprehension and public speaking skills ensuring powerful communicative performance.